Design and development of a digital game to support civics education for fourth-grade students - Moh. Farid Nurul Anwar; Elita Mega Selvia Wijaya; Hediana Woe (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Civics education on the nation's struggle is often considered less interesting to elementary school students. Therefore, this study aims to develop Digital Educational Games as Civics Education learning media based on the History of the Nation's Struggle material for Class IV Elementary School students, with validity and effectiveness. This research uses a research and development model based on the Borg & Gall model, comprising nine stages from needs analysis to field trials. Validation was conducted by media, material, and linguistics experts, with an average validity of 92%, indicating that this media is highly valid for use. The field trial involving 29 students implied that this digital educational game was effective, with an average learning outcome of 95.66 and an effectiveness rate of 90%. Thus, this digital educational game proved to be valid and effective.